Progress Report to the IMFC on the Activities of the Independent Evaluation Office of the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
Since the April 2017 report to the IMFC, the IEO has completed its evaluation on social protection, continued work on evaluations on fragile states and financial surveillance, initiated a new evaluation on advice on unconventional monetary policy, and advanced two updates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Evaluation; IEO Evaluation; IMF Engagement; IMF Exchange Rate Policy Advice; PP; Greece